(untitled) (Modern American Journal of Linguistics, Education, and Pedagogy, 2025)
This article explores innovative approaches to integrating moral and intellectual education in physics lessons. It highlights the potential of applying STEAM methodology, critical thinking, and value-based training to develop students’ responsibility, scientific thinking, environmental awareness, and ethical decision-making skills. The study analyzes how combining academic content with character education fosters the holistic development of learners.